What Impacts Celebrity Endorsement Has On Purchase Decisions - Yuliastuti, Hilda; Sulkifli (Journal of Management, 2024)
Prior studies have demonstrated the impact of celebrity endorsement on consumer buying behaviour. That being said, there is frequently little conversation about the process that links the two variables. The purpose of this study is to investigate brand love as a mediating factor between celebrity endorsements and purchasing decisions. The information was obtained by distributing questionnaires to 153 respondents who were familiar with the brand and understood homogeneous characters, using a purposeful sampling technique. Methods of data analysis with partial least squares (PLS). The findings demonstrated that Brand Love had a mediating role in the noteworthy impact of celebrity endorsements on buying decisions